Contextualising work-family conflict, social support and gender ideologies of professional/registered nurses in the Cacadu District, Eastern Cape - Koeberg, Richenda (Rhodes University, Faculty of Humanities, Department of Psychology, 2015)
The focus of this study was to investigate work-family conflict, social support and gender ideologies of professional/registered nurses in the South African context, specifically within the Cacadu District (Eastern Cape). The study had four aims: (a) to investigate the construct validity of the measuring instrument, (b) to investigate the relationship between social support provided by family and family interference with work (FIW), (c) to ascertain the influence of shift work on perceived work-family conflict, and lastly, (d) to determine whether there is a difference between the number of children in households and nurses' perceptions of work-family conflict. A quantitative research design was used in the study. The sample (N = 106) was taken from five district hospitals in the Cacadu District, Eastern Cape. The measuring instrument consisted of three scales, namely the Multi-dimensional Work-Family Conflict Scale (Carlson, Kacmar, & Williams, 2000), the Social Support Questionnaire (Sarason, Sarason, Shearin, & Pierce, 1987), and an adapted Gender Ideology Scale (Tsai, 2008). The results indicated that the construct validity of the Multi-dimensional Work-Family Conflict scale was satisfactory. However, analysis of the Social Support Questionnaire and Gender Ideology scales both suggested that these scales have not been validated for use with diverse samples outside the contexts in which they were developed. The results also indicated that there is a relationship between social support provided by families and behaviour-based family interference with work. Additionally, there appeared to be a difference between the shifts worked by nurses and their perceived work-family conflict, except for strain-based work interference with family. And lastly, the only significant difference between the number of children in the household and work-family conflict was reported for strain-based work interference with family. The implications of the results for future research suggest the importance of developing and validating work-family conflict, social support and gender ideology scales that are dependent on the context of the research. In so doing, the constructs of the scale are made meaningful. Additionally, the findings provide preliminary evidence of tailoring work-family initiatives that address the needs of the nursing profession and the context of healthcare institutions
Keywords: Nursing -- Social aspects -- South Africa -- Eastern Cape; Nurses -- Job stress -- South Africa -- Eastern Cape; Work and family